Coexistence and Culture: Understanding Human Diversity and Tolerance in Human-Elephant Interactions - Thekaekara, Tarsh; Bhagwat, Shonil A.; Thornton, Thomas F. (Frontiers in Conservation Science, 2021)
There is a growing recognition of the importance of conservation beyond protected areas, in spaces of human-wildlife coexistence. Negative human-wildlife interactions are a key challenge, but a better understanding of the forms of tolerance and mutual accommodation would be useful for coadaptation toward coexistence. To date, however, studies of human-wildlife often have been limited by a largely quantified positivist epistemology, which elide the diverse cultural and ecological contexts which enable tolerance and coexistence between humans and wildlife to develop and adhere. In Gudalur, a plantation landscape in South India, about 150 elephant share space with a quarter of a million people. Using a quantified survey coupled with ethnographic fieldwork, we aim to better understand human diversity and tolerance of elephants that allows for coexistence. We find a marked difference between communities, with ethnicity being a better predictor of tolerance than the more tangible socio-economic or geographic variables such as income, education, land holding or cropping patterns. Using qualitative data, we identify three socio-cultural variables that are relevant to tolerance – a shared history of living with elephants, the mode of subsistence and agricultural crops, and most importantly, ontology or the fundamental understanding of “what is an elephant?” Hunter-gatherer conceptualisations of elephants as “other-than-human persons” prove to be the ontological stance best suited to coexistence, as it allows for elephant individuality and interpersonal negotiations of shared space, which is limited in other world-views, including the worshipping of elephants as Ganesha, the elephant headed deity in the Hindu Pantheon. Having identified some important differences among ethnic communities in human-elephant interactions, we consider the implications of the research for improving the management and practice of human-wildlife coexistence not only in the Nilgiri region but within the broader context of conservation and development.